Developing STEM-Based Interactive E-Books to Improve Students’ Science Literacy - Yuberti, Yuberti; Komikesari, Happy; Lubis, Maesaroh (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this research is to describe the feasibility of the developed STEM-based interactive e-book in improving students' scientific literacy to deal with independent learning policies of independent campuses. Furthermore, this study aims to determine the impact of the developed e-book and investigate students' interest in the e-book. This research employs the ADDIE development model as a type of R&D, including analysis, design, development, implementation, and evaluation. The findings indicate that the STEM-based interactive e-book increases students' scientific literacy skills, with an N-Gain score of 0.56 in the medium category. Based on the expert validation, the developed e-book obtained a percentage of 82.33 % from the material experts, 86.38 % from the media experts, 80.00 % from the IT experts, and 88.09 % from the scientific literacy test instrument experts. All categories belong to the highly feasible criteria. The percentage of students’ responses toward the attractiveness of the e-book was 87.02 %. The developed STEM-based interactive e-book is appropriate for use in education. This study adds new knowledge and experience to developing STEM-based interactive e-books. Besides, providing electronic teaching material in the form of STEM-based interactive e-books can be used to support students’ learning and trigger scientific literacy in the globalization era.